Fetal persistent left superior vena cava in cases with and without chromosomal anomalies. (1st May 2014) - Du, Liu; Xie, Hong‐Ning; Zhu, Yun‐Xiao; Li, Li‐Juan; Peng, Ruan; Zheng, Ju
ABSTRACT Objectives The objectives of this study are to determine and compare the prevalence of persistent left superior vena cava (PLSVC) in chromosomally normal and abnormal fetuses and to evaluate the potential of PLSVC as a screening marker for chromosomal abnormalities. Methods Women undergoing routine fetal sonographic examinations were evaluated once for the presence of PLSVC. PLSVC was diagnosed on the basis of the identification of an additional vessel in the left of the pulmonary artery in a three‐vessel trachea view. Associated abnormalities, karyotypes, and outcomes were analyzed. Results A total of 164 (0.7%, 164/25 171) cases of PLSVC were detected and successfully followed‐up. The detection rates were 0.5% (81/17 535) and 1.1% (83/7636) in the low‐risk and high‐risk cases, respectively. The incidence of PLSVC was lower among the chromosomally or clinically normal (0.4%, 110/24 914) compared with chromosomally abnormal fetuses (7.8%, 20/257, p < 0.001). Additional defects were identified in 90% (18/20) of the PLSVC fetuses with chromosomal anomalies, a rate that was higher than those fetuses with chromosomal normal (61.8%, 68/110). Conclusions Persistent left superior vena cava is more common among chromosomally abnormal than normal fetuses, and PLSVC fetuses with other defects are more highly associated with chromosomal disorders than isolated PLSVC fetuses. Isolated PLSVC is a benign vascular anomaly and may not affect outcomes. © 2014 John Wiley & Sons, Ltd.